The Progressive Mind on Corruption Eradication in Indonesia, A Book Review â€œPemberantasan Tindak Pidana Korupsi Perspektif Hukum Progresifâ€, Yudi Kristiana, Yogyakarta, 2016, 167 pages, ISBN 978-602-1351-55-0 - Astuti, Winda Indri (JILS (Journal of Indonesian Legal Studies), 2021)
Progressive law was born out of anxiety over the operation of the law. This means that progressive law was born from the synthesis of the reality of the operation of law in Indonesia. It is on this basis that this progressive law lives. When legal workers succeed in maintaining the law in a way that is acceptable to society, then at that time the law becomes something that lives the soul and spirit that is maintained by law enforcement becomes a milestone of the death of the law itself. Progressive law can be identified through assumptions, components, goals, verification, spirit, progressiveness, study, contact with other theories, and the agenda of action.